INTERDEPENDENCE BETWEEN JAKARTA STOCK EXCHANGE AND OTHER PACIFIC-BASIN STOCK MARKETS - Noer Azam Achsani (Jurnal Manajemen & Agribisnis, 2004)
International capital markets linkages have been studied since early 90-es.  Most of these studies have mainly focused on the US and other developed markets. There were only a few researches on this topic in the emerging markets.  This paper examines the dynamic linkages among Indonesian and other Pacific-Basin stock markets using correlation analysis, Granger-causality and vector autoregressive (VAR) approach. All the methods give generally similar results. Our empirical results indicate a high degree of international co-movement among the stock price indices.  The degree of integration among these markets after Asian Crisis increased substantially in compare to those before Asian Crisis. The results also show that there are close relationships among the geographically and economically closed markets such as ASEAN markets, New Zealand-Australian and also Hong Kong - South Korea.  The pattern of impulse-response functions illustrates a rapid transmission of stock market events. Shocks in the developed markets are immediately transmitted to other markets. Shocks in the emerging markets are also transmitted to other markets, but without such a big effect comparing to those in the developed markets. The Jakarta stock exchange is strongly correlated with other Pacific-Basin markets, especially with ASEAN markets, Hong Kong and Australia.   The strongest foreign effects for the JSX come from Singapore, Hong Kong and Thailand. They can explain about 5 – 8% of error variance of the Jakarta Index. In contrast, the JSX index can explain 3 - 5 % of their error variances.